Strategy Improving Literacy Financial for Student - Bastian, Elvin; Nur Bhakti Pertiwi, Widya; Fakhrudin, Muhammad; Aris Munandar, Teguh (Management Science Research Journal, 2024)
Study This aim For explore effective strategies in increase literacy finance among students and analyze impact to well-being financial they. Qualitative method with approach studies References used For collect and analyze data from various source academic. Research result show that literacy finance is Skills influential essentials significant to decision finances and welfare financial student. Study This conclude that these strategies can help student develop Skills literacy necessary finances For reach well-being financial period long. Advice given covers integration education finance in curriculum, development technology education financial, approach inclusive, regular training and workshops, collaboration with sector private, as well ongoing program evaluation.